Сomorbidity of coronary artery disease and its significance in predicting the results of coronary artery bypass grafting - V. Yu. Rublev; B. I. Geltser; E. A. Sergeev; V. N. Kotelnikov; R. S. Karpov (Бюллетень сибирской медицины)
The review presents an analysis of the scientific literature on comorbidity of coronary artery disease (CAD) and assessment of its impact on the results of coronary artery bypass grafting (CABG). Arterial hypertension (AH), chronic obstructive pulmonary disease (COPD), metabolic syndrome (MS), and diabetes mellitus (DM) have been shown to be the most common comorbidities in CAD patients. Clinical manifestations of cardiovascular comorbidities also include atrial fibrillation, acute cerebral ischemia, atherosclerosis of carotid and lower limb arteries, and chronic heart failure.Concomitant COPD doubles the risk of postoperative complications after CABG and reduces the 10-year survival rate in patients to 30%. In CAD patients with MS, the risk of postoperative mortality increases by 1.4 times, and the 5-year survival rate decreases by 3 times. Diabetes significantly worsens the long-term survival of patients after CABG and is an independent predictor of acute cardiovascular events after revascularization in the long term. The presence of various comorbidities in CAD patients requires a personalized approach to managing the risks of adverse outcomes after CABG and introduction of modern artificial intelligence (AI) technologies into clinical practice, which significantly increase the accuracy of prognosis.